Analysis and modelling of single domain core-shell (αFeNi/chromite) nanoparticles emitted during selective laser melting, and their magnetic remanence. (10th May 2023) - Dvorsky, Richard; Kukutschová, Jana; Pagáč, Marek; Svoboda, Ladislav; Šimonová, Zuzana; Peterek Dědková, Kateřina; Bednář, Jiří; Mendes, Rafael Gregorio; Matýsek, Dalibor; Malina, Ondřej; Tuček, Jiří; Vilamová, Zuzana; et al.
Abstract: Despite recent intense implementation of increasingly eco-friendly additive manufacturing, the properties of nanoparticulate pollutants emitted during Laser Powder Bed Fusion are still not fully understood, and have generally been overlooked. This study aims to fill this gap in current research by providing new insights into distinct metal/oxide core-shell nanoparticles (3–36 nm) that are produced during 3D printing using stainless steel. It also suggests possible ways for the removal of these potentially harmful by-products. Further, this research also provides a newly developed kinetic model that predicts a metal core growth time of below 200 μs and confirms the predicted theory for the formation of these by-products. In the current study it was found that the cores produced during this process are purely metallic and consist of meteoroid phase kamacite (αFeNi). Within this study there was found to be a complete dominance of single-domain cores of kamacite with prevailing particles below the superparamagnetic threshold showing strong magnetic response and remanence. This new knowledge can be used to minimize potential health risks and reduce contamination of raw materials by this nanoparticulate pollutant, which can adversely affect the quality of printed metal parts, the environment, and the health of the operator. These findings also provide a new possibility of targeted efficient production of superparamagnetic core-shell nanoparticles with a metallic kamacite core during laser powder bed fusion of austenitic steel 316L powder, which can be used in the production of sensors. Graphical abstract: Image 1 Highlights: Stainless steel laser melting emits superparamagnetic core-shell nanoparticles. Highly detailed high-resolution observation of nanoparticulate pollution. Deep and conclusive characterization of emitted nanoparticles. Proposed newly developed kinetic model of nanoparticle core formation and growth. New direction of research in design and development of 3D printers.